Development of triple grades hybrid high-performance steel structure (TGHSS): Concept and experiments. (1st September 2022) - Shi, Gang; Zhao, Huatian; Gao, Yang
Highlights: The triple grades hybrid high-performance steel structure (TGHSS) was proposed. Eight full-scale specimens were tested under cyclic loads. Test phenomena and global seismic performance were introduced. Seismic behaviours, including hysteresis curves, stiffness, deformation, and energy dissipation, were studied. The yielding mechanism among different members was analysed. Abstract: To develop an innovative steel structural system with excellent seismic performance, this paper proposed triple grades hybrid high-performance steel structures (TGHSSs), composed of high strength steel columns, ordinary strength steel beams, and low yield point steel buckling-restrained braces (BRBs). The basic concept was introduced, and then eight full-scale specimens were tested under cyclic loads to validate their seismic behaviour. All the specimens were single-bay and two-story, in which seven specimens are TGHSSs, and a benchmark specimen utilised ordinary strength steel columns for comparisons. In TGHSS specimens, columns included three grades of high strength steel (i.e., 460 MPa, 690 MPa, and 890 MPa), beams utilised 345 MPa steel, and BRBs included three grades of low yield point steel (i.e., 100 MPa, 160 MPa, and 225 MPa). Test observations and structural responses were analysed, involving failure modes, hysteresis behaviour, loading resistance, lateral stiffness, deformation responses, and energy dissipation. The results showed that the TGHSS fulfilled a sequential yielding mechanism as expected with satisfactory seismic behaviour. Specifically, the low yield point steel BRBs yielded at first (overall drift ratio 1/820-1/420) to dissipate seismic energy. Then, the ordinary strength steel beams developed plastic hinges at beam ends (approximate overall drift ratio 2%). At last, the high strength steel columns kept almost elastic or only presented limited plasticity at column bases. Results demonstrated that the proposed TGHSS has strong potential to be an alternative structural system in seismic areas and provides feasible solutions for high-performance structures made of steel having multiple strength grades.